Wpływ zarządzania projektami na kształt struktury organizacji - Kacała, Joanna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The author takes into account the problems with organizational structure designing, concerning project management in organizations and the possibility to use the support of the Project Support Office. These aspects should enable the organization to achieve goals effectively and to obtain commitment of the people. The well designed organizational structure helps the management to determine if there are any problems and if they are important. This is the contrary to situation, where in unadjusted structures important organizational problems are not observed, but the trials for solving unimportant problems are undertaken. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 124-130